A new gains-selection method of depth gauge aided vertical channel for underwater vehicles. (15th June 2023) - Ben, Yueyang; Cui, Wenting; Li, Qian
Highlights: Based on the dominant pole placement technique, a new gains-selection method is proposed to determine the control gains in third-order vertical damping system. The proposed method directly establishes the relationship between the control gains and the system transient response performance. The proposed method provides the explicit design process for the control gains, which decreases the complexity of the gains-selection. Abstract: The third-order vertical channel damping technique is commonly employed to bound the vertical errors, wherein the selection of the gains is critical for system performance. However, the values of conventional gains-selection based on triple pole placement are determined by a complicated trial-and-error process, which is difficult to directly obtain desired system performance. To address this issue, a new gains-selection method based on classical control theory is proposed. In this method, the dominant pole placement technique is adopted to relate the gains to the damping ratio and natural frequency that have a strict correspondence with system transient performance such as settling time and overshoot in typical second-order system. Therefore, the relationship between the gains and the system transient performance is directly established. Then according to the transient response requirements, the values of the gains can be determined conveniently. Finally, the results of simulation and trial demonstrate the feasibility of this method.